PENGARUH SUPERVISI AKADEMIK DAN KOMUNIKASI KEPALA SEKOLAH TERHADAP PRODUKTIVITAS SEKOLAH DI SEKOLAH DASAR NEGERI KECAMATAN TEBAS - Tino, . (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract This study aims to find out the description (1) academic supervision, principal communication, and school productivity (2) influence of academic supervision on school productivity (3) influence of principal's communication on school productivity (4) influence of academic supervision and principal communication together To school productivity. This research uses quantitative approach with analytical descriptive method. The subject in this research is civil servant teacher in SD Negeri Tebas subdistrict with the sample amounted to 137 teachers. Based on the hypothesis testing can be concluded (1) Academic supervision in SD Negeri Tebas District implemented effectively, (2) Communication Principal in SD Negeri Tebas District effectively implemented, (3) School Productivity in SD Negeri Tebas Sub-district is very high, (4) Supervision academic influential To school productivity in SD Negeri Tebas Sub-district, (5) Principal Communication has an effect on school productivity in SD Negeri Tebas Sub-district, (6) Supervision of academic and communication of principal has an effect on school productivity in SD Negeri Tebas sub-district by 22% and the rest is influenced by other factors outside research variabel. Keywords : Academic Supervision, Communication, Productivity School